The Ascension to God in the De Musica of Saint Agustin of Hippo - Arana Alencastre, Jean Luis (2021)
The quest for God has been a major one in the ancient world. And the question about God as Principle, one of the most important and interesting among the classics. Among the conceptions of God, the Augustinian one considers him as a personal God and as the Being itself. In his De Musica, there is an epistemological path through the rhythm to the eternal harmonies which are in the Being. How is the ascent of the soul possible? Which path did he indicates? This article tries to explain both subjects. First, we will analyze the ascent in Augustine and then how that ascent is possible through rhythm to the eternal harmonies.